PENGARUH SIKAP DAN KEBIASAAN BELAJAR SISWA TERHADAP HASIL BELAJAR PADA MATA EKONOMI KELAS XI IPS DI SMA ADABIAH I PADANG - Cintia Aulia, Ade Maiyuhendri; Akhirmen, Akhirmen; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACT   This study aims to analyze : 1 ) The effect of students learning attitudes towards learning outcomes Economy class XI IPS in high school I Adabiah Padang , 2 ) The influence of study habits on learning outcomes of students of Economics class XI IPS in high school I Adabiah Padang , 3 ) Effect of attitudes and habits learning students learning outcomes in Economics class XI IPS high school I Adabiah. This research is descriptive and associative with a quantitative approach . The study population was all students in class XI IPS high school I Adabiah Padang , amounting to 184 people . Sampling technique with proportional random sampling with a sample size of 65 people. Data analysis techniques: descriptive analysis and inductive analysis, namely normality test, multikoleniaritas, heteroscedasticity test, autocorrelation test and multiple regression analysis with SPSS version 16. The results showed that: 1) there is a significant and positive influence students learning attitudes towards learning outcomes Economy class XI IPS in high school I Adabiah Padang obtained by using the t test was 11.0338 with      (Sig= 0.000). 2) there is a significant and positive influence study habits of students on learning outcomes Economy class XI IPS in high school I Adabiah Padang obtained by using the t test was 7.369 with     (Sig = 0.000). 3) there is a significant and positive influence attitudes and study habits of students together to learn the results of IPS XI Economy class in high school I Adabiah Padang (Sig = 0.000) with a contribution rate of 71.80 %. Based on the research results, it is expected that teachers should be more attention to students in classroom management during lessons, so that when the teacher explains all students to listen and concentrate for students are also expected to be able to change the attitudes and study habits for learning success depends on how attitudes and one study habits